Antibacterial activity of Lactobacillus plantarum isolated from Tibetan yaks. (February 2018) - Wang, Lei; Zhang, Hui; Rehman, Mujeeb Ur; Mehmood, Khalid; Jiang, Xiong; Iqbal, Mujahid; Tong, Xiaole; Gao, Xing; Li, Jiakui
Abstract: The main purpose of our study was to isolate the Lactobacillus strains from Tibetan yaks, which may have antibacterial activity. Three Lactobacillus plantarum ( L. plantarum ) strains named LP1, LP2, LP3 and one Pediococcus pentosaceus ( P. pentosaceus ) named PT2 were isolated from fecal samples of Tibetan yaks. We regarded indigenous Escherichia coli ( E. coli ATCC 25922) and Staphylococcus aureus ( S. aureus ATCC 25923) as indicator pathogens. The Bacteriocins derived from these isolated strains manifested high antibacterial activity against E. coli, the highest activity was observed in the case of LP1. On the other hand, PT2 had the most powerful bacteriostatic ability against S. aureus . In addition, all strains were positive for Ent A, which plays an important role in secreting pediocin-like bacteriocins and shows potential probiotic traits of bile and low PH tolerance. Overall, L. plantarum strains in present study could be employed as effective antibacterial substances and can help to remit the problem of antibiotic resistance in veterinary medicine. Highlights: Lactobacillus strains from the faeces of Tibetan yaks that were rearing in free-range environment. L. plantarum isolated from Tibetan yaks were able to inhibit the growth of E. coli and S. aureus. All strains were positive for Ent A, which plays an important role in secreting pediocin-like bacteriocins.